Genome-wide association between single nucleotide polymorphisms with beef fatty acid profile in Nellore cattle using the single step procedure. (December 2016) - Lemos, Marcos; Chiaia, Hermenegildo; Berton, Mariana; Feitosa, Fabieli; Aboujaoud, Carolyn; Camargo, Gregório; Pereira, Angélica; Albuquerque, Lucia; Ferrinho, Adrielle; Mueller, Lenise; Mazalli, Monica; Furlan, Joyce; et al.
Abstract Background Saturated fatty acids can be detrimental to human health and have received considerable attention in recent years. Several studies using taurine breeds showed the existence of genetic variability and thus the possibility of genetic improvement of the fatty acid profile in beef. This study identified the regions of the genome associated with saturated, mono- and polyunsaturated fatty acids, and n-6 to n-3 ratios in theLongissimus thoracis of Nellore finished in feedlot, using the single-step method. Results The results showed that 115 windows explain more than 1 % of the additive genetic variance for the 22 studied fatty acids. Thirty-one genomic regions that explain more than 1 % of the additive genetic variance were observed for total saturated fatty acids, C12:0, C14:0, C16:0 and C18:0. Nineteen genomic regions, distributed in sixteen different chromosomes accounted for more than 1 % of the additive genetic variance for the monounsaturated fatty acids, such as the sum of monounsaturated fatty acids, C14:1 cis-9, C18:1 trans-11, C18:1 cis-9, and C18:1 trans-9. Forty genomic regions explained more than 1 % of the additive variance for the polyunsaturated fatty acids group, which are related to the total polyunsaturated fatty acids, C20:4 n-6, C18:2 cis-9 cis12 n-6, C18:3 n-3, C18:3 n-6, C22:6 n-3 and C20:3 n-6 cis-8 cis-11 cis-14. Twenty-one genomic regions accounted for more than 1 % of the genetic variance for the group of omega-3, omega-6 and the n-6:n-3 ratio. Conclusions The identification of such regions and the respective candidate genes, such asELOVL5, ESSRG, PCYT1A and genes of theABC group (ABC5, ABC6 andABC10 ), should contribute to form a genetic basis of the fatty acid profile of Nellore (Bos indicus ) beef, contributing to better selection of the traits associated with improving human health.